Peran KOMNAS HAM Dalam Konsistensi Kebebasan Berekspresi Terhadap Pendirian Gereja Baptis Indonesia (GBI) - Umam, Muhammad Khotibul; Suharto, Suharto (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2022)
The purpose of this research is to find out, though, how human rights is involved in mediating the conflict, in a problem, according to the development of temple services in Tlogosari Kulon, Pedurungan district, Semarang city. Based on that goal, the study uses qualitative methods. As for the research location, it is in the Tlogosari Kulon, tPedurungan district, the semarang city. The description done includes data description and data interpretation description. Based on the results of studies it can be known how human rights organizations become an agency that plays an active role in their efforts to educate, study, research, and mediation which are applied in problematic areas to the development of a house of worship in the central city of Semarang, central Java a few years ago. The reasons raised by those concerned about the establishment of religious houses are reasonable and tend to be based solely on assumptions, which, of course, are baseless and likely to divide existing diversity, and injure the values of unity.